Chronic alcohol exposure differentially modulates structural and functional properties of amygdala: A cross‐sectional study. (20th November 2020) - Orban, Csaba; McGonigle, John; Flechais, Remy S.A.; Paterson, Louise M.; Elliott, Rebecca; Erritzoe, David; Ersche, Karen D.; Murphy, Anna; Nestor, Liam J.; Passetti, Filippo; Reed, Laurence J.; Ribeiro, Andre S.; et al.
Abstract: Animal models have shown that chronic alcohol exposure is associated with persistent neuroadaptations in amygdala synaptic function, whereas human studies have consistently reported amygdala grey‐matter volume (GMV) reductions in alcohol dependent patients (ADP). We hypothesised that chronic alcohol use associated with neuroadaptations may entail a reconfiguration of the amygdala's functional interactions and that these mechanisms may be affected by structural atrophy. We compared amygdala resting state functional connectivity (RSFC) using a whole brain seed‐based approach and amygdala GMV in abstinent ADP ( n = 20) and healthy controls (HC; n = 39), balanced for age, gender and levels of head motion. The potential moderating influence of age, cumulative alcohol exposure, abstinence length and head motion was further examined in the two groups separately using correlational analyses. We found increased amygdala RSFC with substantia nigra/ventral tegmental area (SN/VTA) in ADP compared with HC. As expected, amygdala GMV was lower in ADP. Multiple regression analyses of the ADP group showed that amygdala‐SN/VTA RSFC increases were primarily associated with cumulative alcohol exposure rather than age, whereas amygdala GMV reductions were primarily associated with age rather than cumulative alcohol exposure. The same association between age and amygdala GMV was not observed amongst HC. Importantly, amygdala GMV and amygdala‐SN/VTA RSFC were uncorrelated in ADP, and neither measure was correlated with abstinence length. These results suggest that chronic alcohol exposure is associated with persistent elevations in amygdala‐SN/VTA RSFC and accelerated age‐related grey‐matter atrophy through potentially distinct mechanisms. Abstract : Alcohol‐dependent patients in long‐term abstinence expressed higher levels of amygdala‐SN/VTA resting state functional connectivity and lower levels of amygdala grey‐matter volumes than age‐matched healthy controls. Magnitude of amygdala‐SN/VTA functional connectivity was correlated with duration of cumulative alcohol exposure but not with amygdala grey‐matter volumes. These findings suggest distinct processes at play influencing structural and functional properties of amygdala in alcohol dependence.